Clustering of goods in the lustrorezea online shop - Erlinda Erlinda; Febri Haswan (Institute of Computer Science (IOCS), 2023)
Lustrorezea is an online shop that was founded in 2018 and has 150 regular customers. This Lustrorezea online shop sells goods in the form of women's, men's, children's clothing and other items, not all items sell well, there are also items that very popular, and not very popular, therefore we need technology in the form of data mining, data mining can help business people make decisions quickly and precisely. In this research, data grouping uses the Rapid Miner application. By using the Rapid Miner application you can group data more quickly and accurately. The results of this research are the formation of 3 clusters by determining the types of goods that are very popular, best-selling and less-selling. With this data, the owner of Lustrorezea can analyze stock needs so that sales can increase further and minimize losses.